A prospective study on neonatal outcome of preterm births and associated factors in a South Indian tertiary hospital setting - Philip, Tinu; Thomas, Pramod (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In spite of the manifold advances in obstetric care, preterm births are still a nightmare for the obstetrician, the pregnant women and her family. The present study aims to study the neonatal outcome in preterm births and its association with sociodemographic, medical and obstetric risk factors. Methods: A prospective observational study done in the Department of Obstetrics and Gynecology in a tertiary level hospital in South India for a period of two years. Results: Majority of the preterm births in this study were in 32-34 weeks which accounted for 53.43% of the preterm births. The immediate neonatal mortality in this study is around 18.25%. The partner’s occupation, the booking status of the mother is strongly associated with preterm births. Pregnancies above the third order were also significantly associated with risk of preterm birth. 44.8% of preterm births are idiopathic, 18.64% have hypertension complicating pregnancy, 14.4% were multiple pregnancies. Neonatal mortality was 30.8 % in pregnancies with hypertension complicating pregnancies. Most common complication of prematurity in present study was Hyaline Membrane Disease and pneumonia. Conclusions: Preventive measures, early identification of risk factors and strengthening the referral system will improve the outcome of the preterm babies and to ensure a positive pregnancy outcome to all pregnant women.